2017
DOI: 10.1038/s41598-017-06528-x
|View full text |Cite
|
Sign up to set email alerts
|

Reduced expression of the murine HLA-G homolog Qa-2 is associated with malignancy, epithelial-mesenchymal transition and stemness in breast cancer cells

Abstract: Qa-2 is believed to mediate a protective immune response against cancer; however, little is known about the role of Qa-2 in tumorigenesis. Here, we used 4T1 breast cancer cells to study the involvement of Qa-2 in tumor progression in a syngeneic host. Qa-2 expression was reduced during in vivo tumor growth and in cell lines derived from 4T1-induced tumors. Tumor-derived cells elicited an epithelial-mesenchymal transition associated with upregulation of Zeb1 and Twist1/2 and enhanced tumor initiating and invasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 39 publications
(52 reference statements)
0
6
0
Order By: Relevance
“… 63 65 Tumor cells after EMT express high levels of stem surface markers, indicating that these cells have become stem-like cells. 66 68 One interesting study revealed that breast CSCs originate from the fusion of M2-TAMs and breast cancer cells; these hybrid cells overexpress mesenchymal-associated genes and stemness markers. 48 Therefore, it can be said that tumor cells after EMT are likely becoming CSCs to some extent.…”
Section: Tumor Inflammatory Microenvironmentmentioning
confidence: 99%
“… 63 65 Tumor cells after EMT express high levels of stem surface markers, indicating that these cells have become stem-like cells. 66 68 One interesting study revealed that breast CSCs originate from the fusion of M2-TAMs and breast cancer cells; these hybrid cells overexpress mesenchymal-associated genes and stemness markers. 48 Therefore, it can be said that tumor cells after EMT are likely becoming CSCs to some extent.…”
Section: Tumor Inflammatory Microenvironmentmentioning
confidence: 99%
“…4T1 tumor cells are representative of the highly aggressive triple-negative subtype of human breast cancer (62). In the 4T1 cell line, only a small percentage of cells (about 4%) express Qa-2 on the cell surface, and Qa-2 protein levels were further reduced during in vivo tumor growth and in tumor-derived cultured cells (63), suggesting that Qa-2 expression is downregulated during breast cancer development. Cell lines derived from tumors induced by 4T1 in the back skin, or in the mammary fat pad, of syngeneic Balb/c mice elicited a partial epithelial-mesenchymal transition (EMT) and exhibited increased stem cell characteristics and enhanced tumor-initiating and invasive capacities that correlated with reduced Qa-2 expression.…”
Section: The Role Of Qa-2 In Cancermentioning
confidence: 99%
“…Cell lines derived from tumors induced by 4T1 in the back skin, or in the mammary fat pad, of syngeneic Balb/c mice elicited a partial epithelial-mesenchymal transition (EMT) and exhibited increased stem cell characteristics and enhanced tumor-initiating and invasive capacities that correlated with reduced Qa-2 expression. In fact, Qa-2 expression was completely lost in a CD44 high /CD24 med/low cancer stem cell subpopulation (64) isolated from these cell lines (63). This striking result suggests the possibility that Qa-2 is excluded from cancer stem cells, thus contributing to their evasion from immunosurveillance.…”
Section: The Role Of Qa-2 In Cancermentioning
confidence: 99%
See 2 more Smart Citations